2000
DOI: 10.1152/jappl.2000.88.6.2205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cerebral hemodynamic response to rhythmic handgrip

Abstract: The response of the cerebral circulation to exercise has been studied with transcranial Doppler ultrasound (TCD) because this modality provides continuous measurements of blood velocity and is well suited for the exercise environment. The use of TCD as an index of cerebral blood flow, however, requires the assumption that the diameter of the insonated vessel is constant. Here, we examine this assumption for rhythmic handgrip using a spectral index designed to measure trends in vessel flow. Nineteen normal subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 72 publications
5
37
1
1
Order By: Relevance
“…Both methods have been used for the assessment of dCA (Micieli et al, 1994;Roatta et al, 1998;Giller et al, 2000). However, the CBFV response to these tests is very heterogeneous.…”
Section: Methods To Induce Hemodynamic Changesmentioning
confidence: 99%
“…Both methods have been used for the assessment of dCA (Micieli et al, 1994;Roatta et al, 1998;Giller et al, 2000). However, the CBFV response to these tests is very heterogeneous.…”
Section: Methods To Induce Hemodynamic Changesmentioning
confidence: 99%
“…These BP changes affect hemodynamics in the extracerebral compartment, measured as stimulus/task-related changes in SBF and/or volume (SBV) (Kirilina et al, 2012;Takahashi et al, 2011), or even in the cerebral compartment itself (Minati et al, 2011 Another source of systemic component is the influence of the autonomic nervous system (ANS) on the cerebral vasculature (Hamel, 2006;Wahl and Schilling, 1993). For example, Giller et al (2000) showed that a rhythmic handgrip exercise causes a sympathetic-mediated modulation of the hemodynamics in the middle cerebral artery. Cerebral hemodynamics is also affected by parasympathetic and trigemino-vascular activity (Goadsby et al, 1997;Wahl and Schilling, 1993).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…The superficial layer of the extracerebral compartment, i.e. the skin, is also under the influence of the ANS; a good example for this is facial flushing (Drummond, 1999;Drummond and Lance, 1987), which takes place even during a simple static handgrip task (Giller et al, 2000), for example. Kirilina et al (2012) suggest that stimulus/ task-evoked sympathetic arterial vasoconstriction may influence fNIRI signals.…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…This may help to ease some of the barriers to exercise, and increase patient adherence. This form of exercise has been found to result similar reduction in resting arterial blood pressure as that of conventional aerobic therapy, (6) and have beneficial effects, on autonomic nervous system regulation of blood pressure, (7) in improving cerebral haemodynamics (8) and forearm vascular response. (9) In spite of the above fact, very few studies have been conducted to evaluate the effect of IHG training on cardiovascular system, especially on cardiac morphology & functioning.…”
Section: Introductionmentioning
confidence: 89%